Rivaroxaban treatment discontinuation rates in patients with nonvalvular atrial fibrillation in Italian clinical practice: RITMUS-AF - Carmine Pizzi; Leopoldo Pagliani; Luca Dalle Carbonare; Piergiuseppe Agostoni; Egidio Imbalzano; Gennaro Galasso; Gianni Casella; Nicolò Dasseni; Leonardo De Luca; Italo Porto; Biagio Sassone; Davide Tosarello; et al. (PLoS ONE, 2026)
Nonadherence to direct oral anticoagulant (DOAC) therapy exposes patients with nonvalvular atrial fibrillation (NVAF) to an increased risk of ischemic stroke and systemic embolism. Nevertheless, approximately 20% of patients discontinue treatment within the first year. In Italy, data on DOAC discontinuation rates are limited, especially in high-risk populations. RITMUS-AF, a prospective, observational cohort study conducted in 31 centers across Italy, investigated rivaroxaban treatment discontinuation in patients with NVAF in routine clinical practice. It included 805 patients aged ≥18 years with NVAF who were newly initiated on rivaroxaban. The primary endpoint was the proportion of patients who discontinued treatment during a 24-month follow-up. Secondary endpoints included the reasons for discontinuation and self-reported adherence to rivaroxaban therapy. At baseline, most patients were oral anticoagulant (OAC)-naïve (n = 599, 74.4%) and had either symptomatic (n = 364, 45.2%) or asymptomatic (n = 441, 54.8%) NVAF. The overall rate of rivaroxaban discontinuation was 8.9 per 100 patient-years (95% CI: 7.1–11.0). The main reasons for discontinuation were adverse events or physician decisions. After 24 months, high adherence was reported in 90.9% of OAC-non-naïve patients and 61.5% of OAC-naïve patients. Forty-six patients (5.7%) experienced bleeding events (with major bleeding events occurring in <0.5% of cases), and one patient (0.1%) had an ischemic stroke. In the RITMUS-AF study, rivaroxaban treatment was associated with a low treatment discontinuation rate, along with high self-reported adherence and a relatively low incidence of ischemic stroke and bleeding events in a high-risk population, findings that may help inform clinical decision-making on the use of rivaroxaban in routine practice.